Three‐dimensional dixon fat–water separated rapid breathheld imaging of myocardial infarction. Issue 6 (4th April 2013) - Saranathan, Manojkumar; Glockner, James
Abstract : Purpose: To develop a breathhold three‐dimensional (3D) Dixon technique for fat suppressed imaging of myocardial infarction. Materials and Methods: A pulse sequence was developed that uses a radial fan‐beam k ‐space segmentation scheme for efficient coverage of k ‐space, enabling 3D scans in a single breathhold. The sequence uses a dual‐echo bipolar readout to enable Dixon fat–water separation for improved visualization of epicardial and pericardial delayed enhancement. The 3D Dixon method was compared with a conventional 2D fast gradient recalled echo (FGRE) ‐based technique in 25 patients. Results: Pericardial visualization scores and confidence were higher while overall image quality and artifacts were slightly worse for 3D Dixon compared with 2D FGRE. Robust fat suppression was achieved in 21 of 25 cases using the 3D Dixon method. Conclusion: A 3D breathhold method for fat–water separated imaging of myocardial delayed enhancement was developed and validated. J. Magn. Reson. Imaging 2013;38:1362–1368. © 2013 Wiley Periodicals, Inc.